Analysis of Unregistered Child Marriage Practices Through the Lens of Social Norms and Economic Pressures (Case Study in Sukaresmi Village) - Riska Riska; Sri Pramudya Wardhani (Journal of Law and Economics, 2025)
Child marriage is a social phenomenon that remains quite high in Sukaresmi Village, influenced by various social and economic norms. This phenomenon occurs without official registration in accordance with the provisions of Indonesia's Marriage Law, particularly concerning the minimum age requirement of 19 years. This practice is often carried out as a community effort to address social and economic issues, especially among middle-class families and those with relatively low education levels. Economic factors serve as the primary driving force, where families with unstable and limited income choose to marry off their underage children to alleviate economic burdens and simultaneously reinforce poverty rates. On the other hand, social and cultural norms that still uphold traditional values and customary influences strengthen the perception that marriage is a matter of honor and morality in society, leading the community to accept this practice despite its legal prohibition. The existence of this unregistered marriage practice is also accompanied by a lack of legal education and literacy, as well as limited access to information and services from the government. As a result, children who marry secretly often experience school dropouts, are completely dependent on their partners, and are vulnerable to legal and social problems in the future. Therefore, strategic efforts are needed to improve legal, economic, and social norm education to reduce underage marriage practices and protect children's rights.